The Decline of 60/40: Why Venture Capital Matters in Private Portfolios - Anuj Maheshwari, (Utilitas Mathematica, 2025)
The democratization of financial information and the evolution of capital markets in the 21st century have reduced the effectiveness of traditional portfolio allocation strategies, particularly the 60/40 model of equities and bonds pioneered by Harry Markowitz. This paper explores the limitations of the 60/40 portfolio for high-net-worth individuals (HNWIs) and evaluates the potential benefits of adopting allocation strategies similar to institutional investors, specifically emphasizing allocation to venture capital. Using historical performance data from public equities, fixed income, and private markets, especially venture-backed companies that have gone public between 2005 and 2025, the analysis in this paper demonstrates that value created for investor during the private stage of a company’s lifecycle outsizes the value creation in the company’s public stage. By comparing traditional 60/40 portfolio returns with institutions like the Yale Endowment, this paper argues that strategic inclusion of venture capital and other alternatives enhances diversification and risk-adjusted returns for the portfolio. The findings suggest that HNW investors seeking to generate alpha and remain competitive in an evolved and dynamic investment landscape should consider incorporating private markets as a core component of their wealth allocation.